2018
DOI: 10.1021/acs.cgd.8b01294
|View full text |Cite
|
Sign up to set email alerts
|

Additive-Free Morphology Control of Organic Polyhedral Molecular Crystals by the Antisolvent Molecular Geometry: From Rod, Disk, to Cube

Abstract: The role of antisolvent molecular geometry on the determination of the final molecular crystals morphology formed by the reverse antisolvent crystallization (r-ASC) process has been unveiled. Herein, we newly report that the rod-, disk-, and cube-shaped tetra­(4-aminophenyl)­porphyrin molecular crystals were selectively obtained by employing o-, m-, and p-xylene as an antisolvent during r-ASC process with ethanol employed as a good solvent. The X-ray diffraction results of the crystals provide a clear indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…However, polar crystals (such as α-resorcinol, ( R , S )-alanine, and γ-glycine) grown in solution often yield unusual habits that are difficult to predict . Solvent is known to strongly impact the crystal habit causing asymmetric growth at the opposite faces along the polar axis of the polar crystal, ,, while the underlying mechanism of solvent on the growth of anisotropic organic crystals is still ill-understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, polar crystals (such as α-resorcinol, ( R , S )-alanine, and γ-glycine) grown in solution often yield unusual habits that are difficult to predict . Solvent is known to strongly impact the crystal habit causing asymmetric growth at the opposite faces along the polar axis of the polar crystal, ,, while the underlying mechanism of solvent on the growth of anisotropic organic crystals is still ill-understood.…”
Section: Introductionmentioning
confidence: 99%
“…82,83 Moreover, crystal morphology control and co-crystal design also depend on intermolecular forces among solute, solvent and antisolvent molecules. Choi et al 84 investigated the role of antisolvent molecular geometry on the determination of the final molecular crystal morphology, in which rod-, disk-, and cube-shaped tetraIJ4-aminophenyl)porphyrin molecular crystals were selectively obtained by employing o-, m-, and p-xylene as an antisolvent, respectively. Meanwhile, X-ray diffraction results indicate that solute-solvent interactions can influence the crystal morphology directly.…”
Section: Model Compoundmentioning
confidence: 99%
“…[102] In detail, reprecipitation is a method that utilizes the difference in the solubility of organic compounds in different solvents to induce nucleation and growth into nanoparticles by rapidly changing the solvent environment. [103][104][105] This method is suitable for organic materials with significant differences in solubility in two solvents, such as low molecular weight aromatic compounds, small organic dye molecules, and so on. In addition, Yao et al reported an adsorbent-assisted vapor deposition technique in which rectangular crystalline nanowires were prepared using Al 2 O 3 as adsorbent and functional organic small molecule 2,4,5-triphenylimidazole (TPI) as precursor.…”
Section: Strategies For the Precise Preparation Of Low-dimensional Or...mentioning
confidence: 99%